Comparative Study of Personality Characteristics Between Combative and Team Game Players - Patel, Shri Krishna; Singh, Raghvendra (Integrated Journal for Research in Arts and Humanities, 2023)
The purpose of the present investigation was to compare the personality characteristics of players who engage in combative games with those who engage in team games better to comprehend the distinctions between the two categories of players. The study examined 96 male athletes aged 21–26 who competed in intercollegiate competitions in their combative sport. The data was collected with the Big Five Personality Questionnaire by Oliver, P. John & Sanjay Srivastava was used to gather data (1999). The independent samples t-test compared combative game players and team game players. The significance threshold was 0.05. The results showed that combative and team sports differed in Extraversion, Agreeableness, Conscientiousness, and Openness to experience (p<0.05) but not in Neuroticism (p>0.05).